2018
DOI: 10.1016/j.visres.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on post-saccadic oscillations

Abstract: Recent research have shown that the eye movement data measured by an eye tracker does not necessarily reflect the exact rotations of the eyeball. For example, post-saccadic eye movements may be more reflecting the relative movements between the pupil and the iris rather than the eyeball oscillations. Since, accurate measurement of eye movements is important in many studies, it is crucial to identify different factors that influence the dynamics of the eye movements measured by an eye tracker. Previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…sharp crests and valleys), using a method previously described [12]. Each saccade was then modelled as the sum of two Gaussian functions (v sac ) which is designed to be representative of saccadic signals typically found in vHIT, which included post-saccadic oscillations of the iris typically recorded in video methods that track the pupil [36][37][38]. The parameters A, B, t peak and σ were defined as those that minimize the cost function J and were found using iterative gradient descent.…”
Section: Discussionmentioning
confidence: 99%
“…sharp crests and valleys), using a method previously described [12]. Each saccade was then modelled as the sum of two Gaussian functions (v sac ) which is designed to be representative of saccadic signals typically found in vHIT, which included post-saccadic oscillations of the iris typically recorded in video methods that track the pupil [36][37][38]. The parameters A, B, t peak and σ were defined as those that minimize the cost function J and were found using iterative gradient descent.…”
Section: Discussionmentioning
confidence: 99%
“…More elaborated versions of the model, such as the one with force-dependent parameters here considered, can provide accurate fittings of families of saccades. The model parameters could be fitted to determine individual characteristics of the eyes related to the viscoelastic link between iris and eyeball, and to the muscular force in different directions, with possible application to diagnostics [23].…”
mentioning
confidence: 99%
“…A typical approach for analyzing data of this type (several observations from each subject and several subjects) is to fit a Linear Mixed Model (LMM) [23]. Previous research [20] has considered the difference between groups using a single point of the PSO signal (t = 0). Whilst this is informative, we are interested in the joint difference between the PSO at t = 0 and at t = 10.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies showed the effect of pupil size and saccade peak velocity (and saccade amplitude accordingly) on the shape of the PSO signals [18,19]. Mardanbegi et al (2017) observed an aging effect on PSO; increased PSO was linearly associated with age [20]. However, could differences in PSO be observed between age-matched cross cultural, cross racial, or cross genetic populations?…”
Section: Introductionmentioning
confidence: 99%